Association between dietary protein intake and change in grip strength over time among adults of advanced age: Life and Living in Advanced Age: A Cohort Study in New Zealand (LiLACS NZ). (14th June 2021) - Wham, Carol; Moyes, Simon A.; Rolleston, Anna; Adamson, Ashley; Kerse, Ngaire; Teh, Ruth
Abstract: Objective: To determine the association between dietary protein intake and change in grip strength (GS) over time among Māori and non‐Māori of advanced age. Methods: Protein intake was estimated from 2×24h multiple pass recall (MPR) in 554 participants, and GS was measured yearly over five years. Anthropometric, physical activity and health data were collected. Results: The median weight‐adjusted protein intake was low (for Māori and non‐Māori men 1.05 and 0.98g/kg/day; for Māori and non‐Māori women 0.87 and 0.91g/kg/day, respectively). There was a general decrease in GS over five years (mean % change of −2.38 ± 15.32 and −4.49 ± 21.92 for Māori and non‐Māori women and −5.47 ± 16.09 and −1.81 ± 13.16 for Māori and non‐Māori men yearly). Intake of protein was not related to GS at any of the five‐year assessment points nor was it related to change over time. Conclusion: Protein intake was low in this cohort of octogenarians and was not protective against loss of GS over five years.